2012
DOI: 10.1080/02680939.2011.623242
|View full text |Cite
|
Sign up to set email alerts
|

Framing and selling global education policy: the promotion of public–private partnerships for education in low-income contexts

Abstract: Public-private partnerships in education (ePPP) are acquiring increasing centrality in the agendas of international organizations and development agencies dealing with educational affairs. They are designed as an opportunity to correct inefficiencies in the public delivery of education and to mobilize new resources to increase the access to and cost-effectiveness of education in low-income contexts. This article explores the emergence of ePPP as a 'programmatic idea' and, in particular, the semiotic strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
97
0
17

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 49 publications
0
97
0
17
Order By: Relevance
“…In fact, the concept of PPPs in education has many resemblances to the public sector reform programme that public choice theorists have been advocating for decades, as well as to what social scientists have traditionally termed "quasi-markets" in education (see Glennerster 1991;Le Grand 1991) Existing research on quasi-markets, vouchers, and school competition has not reached clear conclusions concerning the costs and benefits of these policies, although it usually raises education equity concerns (Waslander et al 2010;OECD 2012). Despite full awareness of the evidence (or of its absence), influential international organizations and transnational consultancy firms are actively disseminating PPP solutions across a broad range of practice communities (Verger 2012;Lubienski 2014). They see school competition within PPP frameworks as a sort of magic bullet that, once governments have addressed the necessary regulatory issues, has the potential to promote access and improve learning outcomes in very diverse educational settings.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the concept of PPPs in education has many resemblances to the public sector reform programme that public choice theorists have been advocating for decades, as well as to what social scientists have traditionally termed "quasi-markets" in education (see Glennerster 1991;Le Grand 1991) Existing research on quasi-markets, vouchers, and school competition has not reached clear conclusions concerning the costs and benefits of these policies, although it usually raises education equity concerns (Waslander et al 2010;OECD 2012). Despite full awareness of the evidence (or of its absence), influential international organizations and transnational consultancy firms are actively disseminating PPP solutions across a broad range of practice communities (Verger 2012;Lubienski 2014). They see school competition within PPP frameworks as a sort of magic bullet that, once governments have addressed the necessary regulatory issues, has the potential to promote access and improve learning outcomes in very diverse educational settings.…”
Section: Introductionmentioning
confidence: 99%
“…Resting on the superiority of quantitative data, and assumptions of objectivity and replicability, the Knowledge Bank has been arguably populated with economically-driven research (Broad, 2006;Rao & Woolcock, 2007a). That the majority of authors cited are trained economists suggests that the research supporting Bank publications on private education is disciplinarily skewed towards a single field of study, one which has been widely critiqued as having an outsize influence on both international development and educational policy (Klees, 2012;Menashy, 2013;Verger, 2012). We argue that from our bibliometric analysis, a policy network can be identified that is reflective of economic imperialism.…”
Section: Discussionmentioning
confidence: 96%
“…Arguments made by Bank staff to support policies involving privately-provided education are argued to employ economist language and mental models that assume the value of markets (Klees et al, 2012;Verger, 2012). In fact, it is the "Economics of Education Group" within the Bank's education sector that has been the main producer of knowledge products on private education from within the organization .…”
Section: "Economic Imperialism" At the World Bankmentioning
confidence: 99%
See 1 more Smart Citation
“…Generalmente, sin embargo, es de reconocer la influencia que las instituciones internacionales poseen y ejercen en la creación de políticas educativas alrededor del mundo, lo cual no ha pasado desapercibido por muchos. (DALE, 1999;EDWARDS, 2013EDWARDS, , 2014MUNDY, 1998;MUNDY y GHALI, 2009;SAMOFF, 2007;2009;VERGER, 2012;VERGER, NOVELLI y ALTINYELKEN, 2012).…”
Section: Introductionunclassified